Visible-light-driven nano-composite fresh-keeping film for ethylene degradation and preparation method and application thereof

By loading nano-TiO2, ChlZn and CaCl2 onto polylactic acid substrates, electrospun nanocomposite preservation films were prepared, solving the problem of low photocatalytic efficiency of TiO2 and achieving efficient ethylene degradation and fruit preservation under visible light.

CN123027697APending Publication Date: 2026-11-03NANJING FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285174.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

The existing TiO2 photocatalytic efficiency is low and the visible light utilization rate is insufficient, making it difficult to effectively catalyze the degradation of ethylene, which leads to post-harvest ripening and senescence of fruits.

Method used

A nanocomposite food preservation film was prepared by electrospinning using polylactic acid (PLA) as the film-forming substrate and loaded with nano-TiO2, sodium zinc chlorophyll (ChlZn), and calcium chloride (CaCl2) as functional modifying components. The optimized component ratio was 0.64 g/L TiO2, 1.80 g/L CaCl2, and 0.186 g/L ChlZn to improve photocatalytic performance.

Benefits of technology

It can efficiently catalyze the decomposition of ethylene under visible light, delay fruit ripening and senescence, significantly extend shelf life, and has excellent mechanical properties while being environmentally friendly and harmless.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027697A_ABST
    Figure CN123027697A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano composite preservative film that visible light catalyzes ethylene degradation and its preparation method and application, belong to food preservation technical field, the nano composite preservative film is with polylactic acid as film-forming substrate, load nanometer titanium dioxide, sodium zinc chlorophyll and calcium chloride, and is prepared by electrospinning process;The nano composite preservative film is with polylactic acid as matrix, with nanometer titanium dioxide, sodium zinc chlorophyll and calcium chloride as functional modified component, and the total addition amount of functional modified component accounts for 5%~20% of polylactic acid matrix.The nano composite preservative film of the application load Chl Zn And Ca 2+ Make the photoconductive response of sample enhance, photoinduced carrier effectively migrates, effectively inhibit the rapid recombination of photoinduced electron-hole, with the performance of catalyzing degradation ethylene under visible light, can efficiently catalyze decomposition ethylene released by fruit under natural light, improve natural light utilization rate, can effectively delay fruit postharvest softening, rot, metamorphic, significantly prolong the shelf life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of food preservation technology, specifically to a nanocomposite preservation film for visible light-catalyzed ethylene degradation, its preparation method, and its application. Background Technology

[0002] Fruits have a high water content and are rich in various nutrients. Their vigorous post-harvest respiration and metabolism make them prone to aging. They are also susceptible to microbial contamination, leading to spoilage and significant economic losses. Ethylene, a plant ripening hormone, is a key substance regulating post-harvest fruit metabolism. Ethylene accelerates fruit respiration, promotes metabolic enzyme activity, and increases cell membrane permeability, ultimately causing softening and spoilage. Therefore, effectively controlling the adverse effects of ethylene during fruit storage and transportation is fundamental to reducing losses and preserving and increasing fruit value.

[0003] With the continuous development of science and technology, nanotechnology is widely used in the food industry. Compared with traditional food packaging materials, nano-packaging materials have superior performance, biodegradability, and environmental friendliness. Therefore, the development of novel nano-packaging materials has become a research hotspot both domestically and internationally. The future trend lies in how to develop novel, natural, green, and pollution-free biodegradable nano-packaging materials that offer preservation benefits while taking into account the post-harvest characteristics of different fresh foods, while ensuring the advantages of nanotechnology.

[0004] TiO2 is a typical semiconductor material. Under ultraviolet light irradiation with wavelengths less than 387 nm, the electron-hole pairs generated can degrade ethylene into harmless substances such as CO2 and H2O. Simultaneously, due to its unique photocatalytic activity, it exhibits strong antibacterial and bactericidal capabilities after absorbing ultraviolet light energy. Studies have shown that utilizing the photocatalytic properties of nano-TiO2 can not only effectively inhibit the growth of food bacteria but also decompose ripening gases such as ethylene. However, its application in fruit preservation has limitations: TiO2 can only be excited by high-energy ultraviolet light, resulting in low utilization of sunlight; after excitation, TiO2 has a high carrier recombination rate, and photogenerated electron-hole pairs recombine easily, leading to low quantum efficiency and significantly reducing the photocatalytic efficiency of TiO2. Therefore, improving the photocatalytic efficiency of TiO2 is of great significance for degrading ethylene and thus inhibiting post-harvest ripening and senescence of fruits. Summary of the Invention

[0005] Technical Problem Solved: Addressing the shortcomings of existing TiO2 photocatalytic efficiency and insufficient visible light utilization, this invention provides a visible light-catalyzed nanocomposite preservation film for ethylene degradation, its preparation method, and its application. Polylactic acid (PLA) is used as the film-forming substrate, and nano-TiO2 is used as the core material for catalyzing ethylene degradation. Sodium zinc chlorophyll (Chl) is added. ZnUsing calcium chloride (CaCl2) as functional modifying components, a nanocomposite preservation film capable of catalytic degradation of ethylene under visible light was prepared by electrospinning. This nanocomposite preservation film has the ability to catalytically degrade ethylene under visible light, and can efficiently catalytically decompose the ethylene released by the fruit under natural light, thereby improving the utilization rate of natural light and achieving the purpose of delaying the ripening and senescence of the fruit.

[0006] Technical Solution: The present invention provides a visible light-catalyzed nanocomposite preservation film for ethylene degradation. The nanocomposite preservation film uses PLA as the film-forming substrate and is loaded with nano-TiO2 and Chl. Zn The nanocomposite food preservation film is prepared by electrospinning with CaCl2; the film uses PLA as the matrix and nano-TiO2 and Chl as the components. Zn CaCl2 is a functional modifying component, and the total amount of the functional modifying component added accounts for 5% to 20% of the PLA matrix.

[0007] Preferably, the nano-TiO2 and Chl Zn The mixing ratio of nano-TiO2 and CaCl2 is as follows: 0.4-0.8 g / L for nano-TiO2, 1.0-2.0 g / L for CaCl2, and Chl... Zn The dosage is 0.1-0.2 g / L.

[0008] Preferably, the nano-TiO2 and Chl Zn The mixing ratio of nano-TiO2 and CaCl2 is as follows: 0.64 g / L of nano-TiO2, 1.80 g / L of CaCl2, and 1 g / L of Chl. Zn The dosage is 0.186 g / L.

[0009] Preferably, the total amount of the functional modified components added accounts for 15% of the PLA matrix.

[0010] This invention also discloses a method for preparing a nanocomposite food preservation film, comprising the following steps: Step 1: Prepare the mother liquor: Take nano TiO2 and Chl respectively Zn CaCl2 was dissolved in HFIP and ultrasonic-assisted stirring was used to ensure complete and uniform dissolution, yielding TiO2 and Chl2, respectively. Zn HFIP stock solution with CaCl2, set aside to stand for later use; Step 2, Prepare spinning solution: Weigh PLA, add TiO2 and Chl prepared in Step 1 Zn Mix CaCl2 / HFIP mother liquor, stir to dissolve and homogenize it, and obtain spinning solution. Degas and let stand for later use. Step 3: Preparation of nanofiber membrane: The spinning solution obtained in step 2 is injected into an injection pump for electrospinning to obtain a nanocomposite food preservation film.

[0011] Preferably, the ultrasonic treatment conditions in step 1 are: temperature 15℃, frequency 50 kHz, and time 20 min.

[0012] Preferably, the stirring in step 2 is magnetic stirring, and the stirring time is 4-6 hours.

[0013] Preferably, the parameters for electrospinning in step 3 are: distance between spinneret and collector 12-18 cm, voltage 15-20 kV, solution propulsion speed 1.0-1.5 mL / h, collector rotation speed 150-250 r / min, ambient temperature 20-30℃, and relative humidity 40%-60%.

[0014] Preferably, the parameters for electrospinning in step 3 are: a distance of 15 cm between the spinneret and the collector, a voltage of 18 kV, a solution propulsion speed of 1.3 mL / h, a collector rotation speed of 200 r / min, an ambient temperature of 25 ± 1 °C, and a relative humidity of 50 ± 5%.

[0015] The present invention also discloses the application of the above-mentioned nanocomposite preservation film or the nanocomposite preservation film prepared by the above-mentioned method in fruit preservation, wherein the fruit includes, but is not limited to, apricot, cherry tomato or plum.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. This invention optimizes the component blending ratio of the nanocomposite food preservation film, clarifies the regulatory law of each component on the photoconductivity of the composite food preservation film through single-factor experiments, and further determines the optimal composition of nano-TiO2 and Chl using response surface methodology. Zn The optimal ratio of TiO2, CaCl2, and Chloride for optimal photoconductivity is: TiO2 0.64 g / L, CaCl2 1.80 g / L, Chloride 1.80 g / L. Zn The dosage was 0.186 g / L; based on this compounding ratio, composite nano-preservative films with total addition amounts of 5%, 10%, 15%, and 20% were prepared. Experiments ultimately determined that the optimal concentration for ethylene degradation was 15% TiO2-Chl. Zn -Ca 2+ Composite nano-preservative film; 2. The nanocomposite food preservation film of the present invention has good mechanical properties and hydrophobic properties, and contains 15% TiO2-Chl. Zn -Ca 2+ The tensile strength of the nanocomposite preservation film is about 3.5 MPa. Under normal room temperature test conditions, the water contact angle of the nanocomposite preservation film is about 120°, which is greater than 90°, showing strong hydrophobic properties, which is beneficial to reduce moisture loss during fruit storage. 3. The nanocomposite food preservation film of the present invention has good photoconductivity, with 15% TiO2-Chl. Zn-Ca 2+ The nanocomposite food preservation film exhibits balanced and excellent light absorption performance in both the ultraviolet and visible light regions, and its light response range is effectively extended to the visible light region. In terms of photoluminescence performance, the nanocomposite food preservation film has the lowest PL intensity, indicating that photogenerated carriers can migrate effectively and effectively suppress the rapid recombination of photogenerated electrons and holes, thereby improving the performance of nano TiO2 in catalyzing the degradation of ethylene in the visible light range. 4. The nanocomposite food preservation film of the present invention has good ethylene degradation performance, with 15% TiO2-Chl Zn -Ca 2+ The nanocomposite food preservation film achieved an ethylene degradation rate of approximately 44.5% under 12-hour testing conditions, and the ethylene degradation efficiency showed a steady upward trend with the extension of the action time, which was significantly better than similar products in the existing technology. 5. The nanocomposite preservation film of this invention can effectively delay the softening, rotting, and spoilage of fruits after harvest, significantly extending their shelf life; the fruits are treated with 15% TiO2-Chl... Zn -Ca 2+ After packaging with nanocomposite preservation film, apricots, cherry tomatoes, and plums were stored at 25℃ and 80% relative humidity for 8 days, with only slight spots appearing on the surface. The rot rate was significantly lower than that of the blank control group without film and the PLA film control group. The rate of decrease in fruit firmness was significantly slowed down. The total color difference ΔE was the lowest, which significantly inhibited the browning and darkening of the fruit. The weight loss rate was lower than that of the control group, which effectively reduced the water loss of the fruit. The peak value of soluble solids content was delayed and the overall fluctuation was smoother. The overall ethylene production rate was significantly lower than that of the control group, the peak value of ethylene release was delayed and the peak value was significantly reduced, which effectively inhibited the ethylene-mediated fruit senescence process. 6. The nanocomposite food preservation film of the present invention uses PLA, nano TiO2, and Chl as film-forming materials. Zn Both CaCl2 and CaCl2 are non-toxic, harmless, and biodegradable, ensuring food safety. They are also environmentally friendly materials that will not harm the environment. Attached Figure Description

[0017] Figure 1 This is a schematic diagram illustrating the working principle of electrospinning of the nanocomposite food preservation film of the present invention. Figure 2 This is a flowchart illustrating the preparation, performance study, and application of the nanocomposite food preservation film of the present invention. Figure 3 Scanning electron microscope (SEM) images of the microstructure of different components of plastic wrap (A: pure PLA film; B: PLA / TiO2 film; C: PLA / TiO2 / Ca...). 2+ Membrane; D is 5% TiO2-Chl Zn -Ca 2+ @PLA membrane; E is 10% TiO2-ChlZn -Ca 2+ @PLA membrane; F is 15% TiO2-Chl Zn -Ca 2+ @PLA membrane (Example 1); G is 20% TiO2-Chl Zn -Ca 2+ @PLA membrane); Figure 4 A comparison chart of the mechanical properties (tensile strength) of different components of food preservation film; Figure 5 Figure 1 shows the water contact angle test results for different components of plastic wrap. Figure 6 The UV-Vis diffuse reflectance spectra of different components of food preservation films; Figure 7 Photoluminescence spectra of different components of food preservation films; Figure 8 The graph shows the ethylene degradation rate of different components of food preservation film as a function of time. Figure 9 The results of appearance changes, color difference, quality indicators and ethylene production rate of apricots after being treated with different plastic wraps and stored at 25℃ and 80% relative humidity for 8 days are shown in the figure. Figure 10 The image shows the changes in appearance, color difference, quality indicators, and ethylene production rate of cherry tomatoes after being treated with different plastic wraps and stored at 25℃ and 80% relative humidity for 8 days. Figure 11 The images show the changes in appearance, color difference, quality indicators, and ethylene production rate of plums after being treated with different plastic wraps and stored at 25℃ and 80% relative humidity for 8 days. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the following will be described in conjunction with the accompanying drawings. Figures 1-11 The technical solutions of the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.

[0019] like Figures 1-2 As shown, this invention discloses a nanocomposite preservation film for visible light-catalyzed ethylene degradation. The nanocomposite preservation film uses PLA as the film-forming substrate and is loaded with nano-TiO2 and Chl. Zn The nanocomposite food preservation film was prepared by electrospinning with CaCl2; it uses PLA as the matrix and nano-TiO2 and Chl2 as the components. ZnCaCl2 and other functional modifying components are used, with the total amount of these components accounting for 5% to 20% of the PLA matrix. Among these, nano-TiO2 and Chl are included. Zn The preferred mixing ratio of nano-TiO2 and CaCl2 is: 0.4-0.8 g / L for nano-TiO2, 1.0-2.0 g / L for CaCl2, and 1 g / L for Chl. Zn The dosage is 0.1-0.2 g / L.

[0020] Chlorophyll is the most important and common pigment in nature and a crucial component of photosynthesis. Compared to other semiconductor photocatalysts, chlorophyll exhibits superior performance. Chlorophyll and its derivatives possess excellent solar light absorption properties, covering the absorption spectrum from ultraviolet and visible light to near-infrared. Furthermore, chlorophyll can form aggregates to more effectively capture sunlight and transfer charge. Chlorophyll derivatives can be used as donor materials in organic solar cells, achieving effective charge separation and stable photocurrent output. Bio-solar cells based on chlorophyll-simulated natural light systems effectively improve photoelectric conversion efficiency. Copper-containing chlorophyll derivatives promote hole extraction between the light-absorbing layer and the hole transport layer in perovskite photovoltaic devices. Chlorophyll is naturally derived, widely available, easy to extract, safe, reliable, and biodegradable. Therefore, this invention utilizes Chlorophyll... Zn As a photosensitizer to improve the photocatalytic properties of TiO2.

[0021] This invention also discloses a method for preparing a nanocomposite food preservation film, comprising the following steps: Step 1: Prepare the mother liquor: Take nano TiO2 and Chl respectively Zn CaCl2 was dissolved in HFIP and ultrasonically stirred at 15℃, 50kHz, and for 20 minutes to ensure complete and homogeneous dissolution, yielding TiO2 and Chl2, respectively. Zn HFIP stock solution with CaCl2, set aside to stand for later use; Step 2, Prepare spinning solution: Weigh PLA, add TiO2 and Chl prepared in Step 1 Zn Mix CaCl2 / HFIP mother liquor with magnetic stirring for 4-6 hours to ensure complete and uniform dissolution, and obtain spinning solution. Deaerate and let stand for later use. Step 3: Preparation of nanofiber membrane: The spinning solution obtained in Step 2 is injected into an injection pump for electrospinning to obtain a nanocomposite preservation film. The electrospinning parameters are: distance between the spinneret and the collector 12-18 cm, voltage 15-20 kV, solution propulsion speed 1.0-1.5 mL / h, collector rotation speed 150-250 r / min, ambient temperature 20-30℃, and relative humidity 40%-60%. Electrospinning is a micro / nanofiber material preparation technology based on electrostatic forces. The nanofiber membrane prepared by electrospinning has the characteristics of large specific surface area, small pore size, high porosity, and good surface properties. It can effectively block and filter dust and harmful microorganisms while ensuring adequate gas and moisture permeation. By using electrospinning technology to load functional active factors into the fibers, the active substances are encapsulated and released, thereby developing packaging materials with preservation effects, improving the packaging environment of fruits, and ultimately extending the shelf life of fruits.

[0022] This invention also discloses the application of the above-mentioned nanocomposite preservation film or the nanocomposite preservation film prepared by the above-mentioned method in fruit preservation, including but not limited to apricot, cherry tomato or plum and other climacteric fruits that easily release ethylene.

[0023] The present invention will be further described in conjunction with the following specific embodiments.

[0024] Example 1: Combination Figure 1 and Figure 2 As shown, in this embodiment, 15% TiO2-Chl Zn -Ca 2+ The preparation method of @PLA nanocomposite food preservation film is as follows.

[0025] (1) Preparation of the stock solution: Weigh out 0.64g of anatase nano-TiO2, 1.8g of anhydrous CaCl2, and 0.1860g of Chl. Zn Add appropriate amounts of HFIP to each component; each component's mother liquor was subjected to ultrasonic treatment at 15℃, 50kHz, for 20min, and then stirred with a magnetic stirrer at room temperature until completely dissolved; each was transferred to a 10mL volumetric flask, diluted to the mark with HFIP, shaken well, sealed, and allowed to stand for later use, yielding TiO2 / HFIP mother liquor, CaCl2 / HFIP mother liquor, and Chl... Zn / HFIP mother liquor.

[0026] (2) Preparation of spinning solution: Transfer 0.571 mL TiO2 / HFIP mother liquor, 0.571 mL CaCl2 / HFIP mother liquor, and 0.571 mL Chl ZnPour the HFIP stock solution into a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, and stir with a magnetic stirrer for 4 hours at room temperature until completely dissolved. Dilute to the mark with HFIP and continue stirring for 2 hours until homogeneous. After ultrasonic degassing, seal and let stand for later use to obtain 15% TiO2-Chl. Zn -Ca 2+ @PLA spinning solution.

[0027] (3) Electrospinning: The prepared spinning solution was loaded into a 5mL syringe and connected to a 24G spinneret; the electrospinning parameters were set as follows: distance between the spinneret and the roller collector 15cm, applied high voltage 18kV, solution feed rate 1.3mL / h, roller speed 200r / min, ambient temperature 25±1℃, relative humidity 50±5%; the nanofibers were collected in a 20×17.5cm covering. 2 After spinning on an aluminum foil roller, the fiber film is removed from the aluminum foil on the roller for subsequent experiments. The microstructure of the prepared nanocomposite food preservation film is as follows: Figure 3 As shown in F in the diagram.

[0028] Example 2: Combination Figure 1 and Figure 2 As shown, in this embodiment, 5% TiO2-Chl Zn -Ca 2+ The preparation method of @PLA nanocomposite food preservation film is as follows.

[0029] (1) Preparation of mother liquor: Same as in Example 1.

[0030] (2) Preparation of spinning solution: Transfer 0.19 mL TiO2 / HFIP mother liquor, 0.19 mL CaCl2 / HFIP mother liquor, and 0.19 mL Chl Zn Pour the HFIP stock solution into a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, and stir with a magnetic stirrer for 4 hours at room temperature until completely dissolved. Dilute to the mark with HFIP and continue stirring for 2 hours until homogeneous. After ultrasonic degassing, seal and let stand for later use to obtain 5% TiO2-Chl. Zn -Ca 2+ @PLA spinning solution.

[0031] (3) Electrospinning: Same as in Example 1. The microstructure of the obtained nanocomposite food preservation film is as follows: Figure 3 As shown in D in the diagram.

[0032] Example 3: Combination Figure 1 and Figure 2 As shown, in this embodiment, 10% TiO2-Chl Zn -Ca 2+ The preparation method of @PLA nanocomposite food preservation film is as follows.

[0033] (1) Preparation of mother liquor: Same as in Example 1.

[0034] (2) Preparation of spinning solution: Transfer 0.381 mL TiO2 / HFIP mother liquor, 0.381 mL CaCl2 / HFIP mother liquor, and 0.381 mL Chl Zn Pour the HFIP stock solution into a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, and stir with a magnetic stirrer for 4 hours at room temperature until completely dissolved. Dilute to the mark with HFIP and continue stirring for 2 hours until homogeneous. After ultrasonic degassing, seal and let stand for later use to obtain 10% TiO2-Chl. Zn -Ca 2+ @PLA spinning solution.

[0035] (3) Electrospinning: Same as in Example 1. The microstructure of the obtained nanocomposite food preservation film is as follows: Figure 3 As shown in E in the figure.

[0036] Example 4: Combination Figure 1 and Figure 2 As shown, in this embodiment, 20% TiO2-Chl Zn -Ca 2+ The preparation method of @PLA nanocomposite food preservation film is as follows.

[0037] (1) Preparation of mother liquor: Same as in Example 1.

[0038] (2) Preparation of spinning solution: Transfer 0.762 mL TiO2 / HFIP mother liquor, 0.762 mL CaCl2 / HFIP mother liquor, and 0.762 mL Chl Zn Pour the HFIP stock solution into a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, and stir with a magnetic stirrer for 4 hours at room temperature until completely dissolved. Dilute to the mark with HFIP and continue stirring for 2 hours until homogeneous. After ultrasonic degassing, seal and let stand for later use to obtain 20% TiO2-Chl. Zn -Ca 2+ @PLA spinning solution.

[0039] (3) Electrospinning: Same as in Example 1. The microstructure of the obtained nanocomposite food preservation film is as follows: Figure 3 As shown in G.

[0040] Comparative Example 1: The preparation method of pure PLA plastic wrap in this comparative example is as follows.

[0041] Weigh 1g of PLA and add it to a 10mL volumetric flask. Add an appropriate amount of HFIP and stir with a magnetic stirrer for 4 hours at room temperature until completely dissolved. Make up to the mark with HFIP and continue stirring for 2 hours until homogeneous. After ultrasonic degassing, seal and let stand for later use to obtain a pure PLA spinning solution. Inject the spinning solution into a 5mL syringe pump for electrospinning, using the same parameters as in Example 1, to obtain a pure PLA food preservation film. The microstructure of the obtained food preservation film is as follows: Figure 3 As shown in A in the diagram.

[0042] Comparative Example 2: The preparation method of PLA / TiO2 food preservation film in this comparative example is as follows.

[0043] (1) Preparation of mother liquor: Weigh 0.64g of anatase nano TiO2, add an appropriate amount of HFIP, and perform ultrasonic treatment with a probe at 15℃ for 20min at a frequency of 50KHz. Stir with a magnetic stirrer at room temperature until completely dissolved, transfer to a 10mL volumetric flask, dilute to the mark with HFIP, shake well, seal and let stand for later use to obtain TiO2 / HFIP mother liquor.

[0044] (2) Preparation of spinning solution: Transfer 0.19 mL of TiO2 / HFIP mother liquor to a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, stir with a magnetic stirrer for 4 h at room temperature until completely dissolved, dilute to the mark with HFIP, continue stirring for 2 h until evenly mixed, degas by ultrasonication, seal and let stand for later use to obtain PLA / TiO2 spinning solution.

[0045] (3) Electrospinning: Same as in Example 1. The microstructure of the obtained PLA / TiO2 food preservation film is as follows: Figure 3 As shown in B in the diagram.

[0046] Comparative Example 3: In this comparative example, PLA / TiO2 / Ca 2+ The preparation method of plastic wrap is as follows.

[0047] (1) Preparation of mother liquor: Weigh 0.64g of anatase nano TiO2 and 1.8g of anhydrous CaCl2 respectively, add an appropriate amount of HFIP, and perform ultrasonic treatment of each component mother liquor at 15℃ with a frequency of 50KHz for 20min. Stir with a magnetic stirrer at room temperature until completely dissolved, transfer to 10 mL volumetric flasks, dilute to the mark with HFIP, shake well, seal and stand for later use to obtain TiO2 / HFIP mother liquor and CaCl2 / HFIP mother liquor respectively.

[0048] (2) Preparation of spinning solution: Transfer 0.19 mL of TiO2 / HFIP mother liquor and 0.19 mL of CaCl2 / HFIP mother liquor to a 10 mL volumetric flask, add 1 g PLA, add an appropriate amount of HFIP, and stir with a magnetic stirrer for 4 h at room temperature until completely dissolved. Dilute to the mark with HFIP, continue stirring for 2 h until homogeneous, ultrasonically degas, seal and let stand for later use to obtain PLA / TiO2 / CaCl ... 2+ Spinning solution.

[0049] (3) Electrospinning: Same as in Example 1. The obtained PLA / TiO2 / Ca... 2+ The microstructure of plastic wrap is as follows Figure 3 As shown in C.

[0050] Performance tests were conducted on Examples 1-4 and Comparative Examples 1-3, and the results are as follows: (1) Mechanical properties: Mechanical stress was tested using a texture analyzer, and the results are as follows: Figure 4 As shown. Example 1 of the present invention (15% TiO2-Chl) Zn -Ca 2+ The nanocomposite food preservation film obtained by @PLA) exhibited good mechanical properties, with a mechanical stress reaching 3.5 MPa; while the food preservation film of Comparative Example 1 (pure PLA), Comparative Example 2 (PLA / TiO2), and Comparative Example 3 (PLA / TiO2 / Ca) showed better mechanical properties. 2+ The mechanical stress of plastic wrap is only 2.62MPa, 2.23MPa, and 1.96MPa.

[0051] (2) Water contact angle: The water contact angle was measured using a video optical contact angle meter; a drop of approximately 1 μL of ultrapure water was carefully placed on the surface of the cling film, and three measurements were taken for each film at 25°C, and the average value was recorded. Figure 5 As shown, the plastic wrap samples in each group are: PLA; PLA / TiO2; PLA / TiO2 / Ca 2+ ; 5%, 10%, 15%, 20% TiO2 / Ca 2+ / chl Zn @PLA film, water contact angle values ​​and statistical results for each group of plastic wrap: Pure PLA sample water contact angle ≈ 120°, marked a, high hydrophobicity; PLA / TiO2 sample water contact angle ≈ 100°, marked bc, significantly decreased water contact angle compared to pure PLA sample, improved hydrophilicity; PLA / TiO2 / Ca 2+ The sample's water contact angle was approximately 98°. Marked as c, the water contact angle was further reduced, making it the lowest among all groups and exhibiting the strongest hydrophilicity, showing a significant difference from the PLA group; 5% TiO2 / Ca 2+ / chl Zn@The water contact angle of the PLA sample was approximately 121°. Marking a, the water contact angle recovered, reaching the same level as the pure PLA sample, indicating restored hydrophobicity; 10% TiO2 / Ca 2+ / chl Zn The water contact angle of the PLA sample was approximately 118°. Marked as 'a', maintaining a high contact angle, there was no significant difference compared to the pure PLA sample; 15% TiO2 / Ca 2+ / chl Zn The water contact angle of the PLA sample is approximately 120°, marked as a, indicating high hydrophobicity; 20% TiO2 / Ca 2+ / chl Zn The water contact angle of the PLA sample was approximately 112°. The sample labeled ab showed a slightly lower water contact angle, falling between groups a and bc, and was not significantly different from the pure PLA sample. In summary, the water contact angle of the nanocomposite preservation film prepared in Example 1 of this invention is approximately 120°, greater than 90°, under normal room temperature testing conditions, exhibiting strong hydrophobicity.

[0052] (3) Ultraviolet-Visible Diffuse Reflectance Spectroscopy: The diffuse reflectance spectrum was obtained by using an ultraviolet-visible spectrophotometer with an integrating sphere accessory, using standard BaSO4 as a reference, and scanning wavelengths from 200 to 800 nm. Figure 6 As shown, the pure PLA sample exhibits weak absorption only in the short ultraviolet region, with almost no light response in the ultraviolet and visible light regions; PLA / TiO2 and PLA / TiO2 / Ca 2+ The sample exhibits strong absorption only in the ultraviolet band and almost no absorption in the visible light region, indicating that unmodified TiO2 only possesses ultraviolet light response capability; the introduction of Chl Zn After modification, TiO2 / Ca 2+ / Chl Zn The series of composite food preservation films, while retaining strong absorption in the ultraviolet region, exhibit a characteristic absorption peak of zinc chlorophyll in the 400-700nm visible light range, confirming that the material's light response range has been successfully broadened into the visible light region. With Chl... Zn As the amount added increases, the absorbance of the plastic wrap across the entire wavelength range gradually increases; among them, the 15% TiO2 / Ca content obtained in Example 1... 2+ / Chl Zn The @PLA sample exhibited balanced and excellent light absorption performance in both the UV and visible light ranges, compared to 20% TiO2 / Ca. 2+ / Chl Zn The PLA sample, while achieving good light response, also takes into account the hydrophobic properties of the film surface, providing a good foundation for visible light-driven functional food preservation films.

[0053] (4) Photoluminescence Spectroscopy: The photoluminescence performance was tested using a fluorescence spectrometer with 405 nm as the excitation wavelength. The photoluminescence (PL) emission spectra of the composite film in the 450-700 nm range were obtained. Figure 7 As shown, pure PLA sample, PLA / TiO2 sample, and PLA / TiO2 / Ca sample... 2+ The sample showed almost no significant fluorescence emission under these excitation conditions; TiO2 / Ca 2+ / chl Zn The PLA series composite food preservation film exhibits a characteristic fluorescence emission peak of zinc chlorophyll at 665-670 nm, along with the Chl... Zn As the addition amount increased from 5% to 15%, the fluorescence emission intensity of the thin film gradually decreased; in Example 1 of this invention, 15% TiO2 / Ca 2+ The PL fluorescence intensity of the / chl-Zn@PLA sample reached its lowest value, indicating that TiO2 / Ca 2+ With Chl Zn The constructed heterojunction can promote the efficient migration of photogenerated carriers and significantly suppress the rapid recombination of photogenerated electron-hole pairs; when Chl Zn When the addition amount was further increased to 20%, the fluorescence intensity actually rebounded. Excess filler agglomerated, introducing additional carrier recombination centers and exacerbating electron-hole recombination. This result was corroborated by the UV-Vis diffuse reflectance spectroscopy results, indicating that the composite preservation film with a 15% addition ratio has both excellent light-harvesting ability and high efficiency in separating photogenerated carriers.

[0054] (5) Ethylene degradation performance test: Cut 8cm×8cm samples of each component of the cling film, place them on one side of a 250mL glass bottle and seal with a rubber stopper. Collect 99% pure ethylene gas using an aluminum foil composite film gas sampling bag. Inject a certain concentration of ethylene gas into the glass bottle and determine the initial ethylene concentration in the container using a portable ethylene analyzer; at 23.2W / m 2 Under LED visible light irradiation, at 25±2℃ and 45±2%RH, the ethylene degradation performance of different component food preservation film samples was tested for 12 hours. Each sample underwent three parallel tests simultaneously, and the results are expressed as the average value. The ethylene concentration in the container was monitored every 2 hours. Figure 8 As shown, pure PLA samples have almost no ethylene degradation ability; PLA / TiO2 and PLA / TiO2 / Ca 2+ The sample exhibited extremely low ethylene degradation rate under visible light conditions, indicating that the TiO2-based system alone is insufficient for ethylene degradation under visible light-driven conditions; the introduction of Chl... Zn After the photosensitizer is formed, TiO2 / Ca 2+ / Chl ZnThe PLA series films exhibited significant visible light ethylene degradation activity, with the ethylene degradation rate continuously increasing with prolonged irradiation time; Example 1 showed a 15% TiO2 / Ca... 2+ / chl Zn The PLA sample exhibited the best ethylene degradation performance, with an ethylene degradation rate of 44.5% after 12 hours; when Chl Zn When the addition amount is reduced to 5%, insufficient active sites lead to a decrease in ethylene degradation capacity; when the addition amount is increased to 20%, filler agglomeration intensifies photogenerated carrier recombination, resulting in a decline in ethylene degradation performance. In summary, 15% TiO2 / Ca... 2+ / chl Zn The @PLA sample represents the optimal filler concentration for this system. This result is consistent with the characterization results of UV-Vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. Thanks to the excellent visible light capture capability and efficient photogenerated carrier separation efficiency of the preservation film under this ratio, the composite preservation film is endowed with excellent ethylene removal capability and has application potential in the field of fruit and vegetable preservation.

[0055] (6) Figures 9-11 The images show the results of preservation treatments on apricots, cherry tomatoes, and plums, including those using film-free preservation, a PLA film-based control group, and a 15% TiO2 / Chl treatment. Zn / Ca 2+ @PLA nanocomposite preservation film (Example 1) experimental group preservation, appearance changes after 8 days of storage at 25℃ and 80% relative humidity (PLA nanocomposite preservation film). Figure 9 , Figure 10 , Figure 11 ), color difference ( Figure 9 A, Figure 10 A, Figure 11 A) Hardness, weight loss rate, soluble solids content, and decay rate ( Figure 9 BE Figure 10 BE Figure 11 BE) and ethylene production rate ( Figure 9 F, Figure 10 F, Figure 11The results are shown in Figure F). The results show that the composite nano-preservative film obtained in Example 1 of this invention can effectively delay the post-harvest decay, spoilage, softening and other quality deterioration of apricots, cherry tomatoes and plums: ① Appearance: Apricots, cherry tomatoes and plums with nano-composite preservative film only showed slight spots on the surface, and the decay rate was significantly lower than that of the blank control group without film and the PLA film control group; ② Hardness: The rate of decrease in hardness of apricots, cherry tomatoes and plums with nano-composite preservative film was significantly slowed down; ③ Color: The total color difference ΔE of apricots, cherry tomatoes and plums with nano-composite preservative film was the lowest, which significantly inhibited the browning and darkening of the fruit; ④ Weight loss rate: The weight loss rate of nano-composite preservative film was lower than that of the blank control group without film and the PLA film control group, which effectively reduced the water loss of the fruit; ⑤ Soluble solids: The peak value of soluble solids content of nano-composite preservative film was delayed and the overall fluctuation was smoother; ⑥ Ethylene generation: The overall ethylene generation rate of nano-composite preservative film was significantly lower than that of the two control groups, the peak value of ethylene release was delayed and the peak value was significantly reduced, which effectively inhibited the ethylene-mediated fruit senescence process.

[0056] In summary, the nanocomposite preservation film of the present invention, through loading Chl Zn and Ca 2+ This enhances the photoconductive response of the sample, facilitates the effective migration of photogenerated carriers, and effectively suppresses the rapid recombination of photogenerated electrons and holes, thereby improving the performance of nano-TiO2 in catalyzing ethylene degradation in the visible light range. This nanocomposite preservation film can be used for fruit preservation, effectively delaying post-harvest softening, rotting, and spoilage of fruits, and significantly extending the shelf life.

[0057] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A nanocomposite food preservation film for visible light-catalyzed ethylene degradation, characterized in that, The nanocomposite food preservation film is prepared by electrospinning using polylactic acid as the film-forming substrate and loaded with nano-titanium dioxide, sodium zinc chlorophyll and calcium chloride. The nanocomposite food preservation film uses polylactic acid as the matrix and nano-titanium dioxide, sodium zinc chlorophyll and calcium chloride as functional modifying components. The total amount of the functional modifying components added accounts for 5% to 20% of the polylactic acid matrix.

2. The visible light-catalyzed ethylene degradation nanocomposite preservation film according to claim 1, characterized in that, The compounding ratio of nano-titanium dioxide, sodium zinc chlorophyll salt, and calcium chloride is as follows: the amount of nano-titanium dioxide is 0.4-0.8 g / L, the amount of calcium chloride is 1.0-2.0 g / L, and the amount of sodium zinc chlorophyll salt is 0.1-0.2 g / L.

3. The visible light-catalyzed ethylene degradation nanocomposite preservation film according to claim 2, characterized in that, The compounding ratio of nano-titanium dioxide, sodium zinc chlorophyll salt, and calcium chloride is as follows: 0.64 g / L of nano-titanium dioxide, 1.80 g / L of calcium chloride, and 0.186 g / L of sodium zinc chlorophyll salt.

4. The visible light-catalyzed ethylene degradation nanocomposite preservation film according to claim 1, characterized in that, The total amount of the functional modified components added accounts for 15% of the polylactic acid matrix.

5. A method for preparing a nanocomposite food preservation film as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Prepare the mother liquor: Dissolve nano-titanium dioxide, sodium zinc chlorophyll, and calcium chloride in hexafluoroisopropanol, respectively. Use ultrasonic-assisted stirring to ensure complete and uniform dissolution, and obtain hexafluoroisopropanol mother liquors of nano-titanium dioxide, sodium zinc chlorophyll, and calcium chloride, respectively. Let stand for later use. Step 2, Prepare spinning solution: Weigh polylactic acid, add nano titanium dioxide, sodium zinc chlorophyll and calcium chloride / hexafluoroisopropanol mother liquor prepared in Step 1, stir to dissolve and homogenize it to obtain spinning solution, deaerate and let stand for later use. Step 3: Preparation of nanofiber membrane: The spinning solution obtained in step 2 is injected into an injection pump for electrospinning to obtain a nanocomposite food preservation film.

6. The method for preparing the nanocomposite food preservation film according to claim 5, characterized in that, The ultrasonic treatment conditions in step 1 are: temperature 15℃, frequency 50 kHz, and time 20 min.

7. The method for the visible light-catalyzed degradation of ethylene nanocomposite preservation film according to claim 5, characterized in that, In step 2, the stirring is done with magnetic stirring for 4-6 hours.

8. The method for preparing the nanocomposite food preservation film according to claim 5, characterized in that, The parameters for electrospinning in step 3 are as follows: distance between spinneret and collector 12-18 cm, voltage 15-20 kV, solution propulsion speed 1.0-1.5 mL / h, collector rotation speed 150-250 r / min, ambient temperature 20-30℃, and relative humidity 40%-60%.

9. The method for preparing the nanocomposite food preservation film according to claim 8, characterized in that, The parameters for electrospinning in step 3 are as follows: distance between spinneret and collector 15cm, voltage 18kV, solution propulsion speed 1.3mL / h, collector rotation speed 200r / min, ambient temperature 25±1℃, and relative humidity 50±5%.

10. The application of a nanocomposite preservation film as described in any one of claims 1-4 or a nanocomposite preservation film prepared by any one of claims 5-9 in fruit preservation, characterized in that, The fruits mentioned include, but are not limited to, apricots, cherry tomatoes, or plums.